The Technical–Tactical Patterns of Scoring Actions in Male Visually Impaired Judokas: A Weight Category Analysis - Alfonso Gutiérrez-Santiago; Anxo Fernández-Moscoso; Xoana Reguera-López-de-la-Osa; Antonio José Silva-Pinto; Juan Carlos Argibay-González; Iván Prieto-Lage (Applied Sciences)
In Para-judo, the technical actions and tactical situations suitable for scoring in a combat have not been studied. The aim of this research was to determine the technical–tactical patterns of scoring actions in Para-judo, focusing on weight categories. An observational methodology was employed to conduct this study. The sample consisted of all male judokas with visual impairment (n = 172) in the senior category who participated in the World Championships held in Odivelas in 2018. A total of 232 combats and 313 scoring actions were analyzed. To obtain the results, we used different analytical techniques with SPSS: descriptive analysis, chi-square test, and T-pattern analysis. The significance level used was p < 0.05. Key findings show that the majority of scoring actions occurred in the first two minutes of combat, highlighting the importance of early initiative. Techniques such as ashi-waza, te-waza, and sutemi-waza demonstrated particular effectiveness across categories, with a focus on movements like sumi-otoshi, ouchi-gari, and ko-soto-gake. Moreover, the most common grip—lapel-sleeve—proved advantageous, aiding judokas in controlling the bout and achieving scores, especially when coupled with effective transition techniques. The study’s weight-specific analysis further revealed distinct patterns, emphasizing the importance of tailored training approaches. For instance, lighter judokas benefited from countering leg attacks with arm or sacrifice techniques to score waza-ari, while heavier judokas favored leg-to-leg counterattacks, often achieving ippon. The results suggest that judokas and coaches could benefit from a more systematic focus on grip stability, strategic positional work, and transition efficiency, particularly from standing to ground. This research contributes valuable insights into optimal techniques and strategies for visually impaired judokas, providing clear guidelines for training and competition.